Proceedings of the Fourth International Conference on Future Energy Systems 2013
DOI: 10.1145/2487166.2487168
|View full text |Cite
|
Sign up to set email alerts
|

Scaling distributed energy storage for grid peak reduction

Abstract: Reducing peak demand is an important part of ongoing smart grid research efforts. To reduce peak demand, utilities are introducing variable rate electricity prices. Recent efforts have shown how variable rate pricing can incentivize consumers to use energy storage to cut their electricity bill, by storing energy during inexpensive off-peak periods and using it during expensive peak periods. Unfortunately, variable rate pricing provides only a weak incentive for distributed energy storage and does not promote i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 17 publications
(31 reference statements)
1
26
0
Order By: Relevance
“…The major benefits of the incorporation of DSM and battery storage systems are to shave the peak power demand and to increase renewable self-consumption, resulting in increased grid stability and reduced distribution system losses. There are two potential energy tariff programs: time-of-use (ToU) and real-time price (RTP) which can provide consumers the benefit of reducing their energy bill by deploying this system [8]. In this work, the RTP based directly on the wholesale market price is considered.…”
Section: Introductionmentioning
confidence: 99%
“…The major benefits of the incorporation of DSM and battery storage systems are to shave the peak power demand and to increase renewable self-consumption, resulting in increased grid stability and reduced distribution system losses. There are two potential energy tariff programs: time-of-use (ToU) and real-time price (RTP) which can provide consumers the benefit of reducing their energy bill by deploying this system [8]. In this work, the RTP based directly on the wholesale market price is considered.…”
Section: Introductionmentioning
confidence: 99%
“…Flat-power pricing is particularly attractive for storage, since it takes much less storage capacity to flatten a home's demand than to shift all of its demand to the lowprice period. We explore this aspect of scheduling storage in recent work [13], although using a peak-based pricing plan based on a home's absolute peak. As we mention, one challenge with peakbased pricing is the difficulty in predicting when the absolute peak will occur.…”
Section: Discussionmentioning
confidence: 99%
“…However, peak-based pricing is not as conducive to algorithmic optimization, since it requires scheduling algorithms to know with high accuracy when the peak will occur each billing period. As part of prior work, we have found that accurately predicting when a peak will occur is challenging [13], hindering load scheduling algorithms that must optimize for the absolute peak. Consumers are typically charged based on their peak usage over an entire month-long billing period, requiring accurate predictions of power usage over a small time window, e.g., fifteen minutes, as far as one month in advance.…”
Section: Advantagesmentioning
confidence: 99%
“…Vytelingum et al [5] and Mishra et al [22] presented a DSM mechanism which assumed the existence of energy storage on consumers' premises. Ganu et al developed a device called nPlug, which can perform scheduling and voltage sensing to identify peak and off-peak periods on the grid [23].…”
Section: Related Workmentioning
confidence: 99%